Red-Brownism: from its post-Soviet foundations to present-day political faultlines - Guerra, Nicola (Informa UK Limited, 2026)
This study examines the emergence and evolution of Red-Brownism, an ideological phenomenon blending elements of the far right and far left in opposition to Western capitalism, globalization, and American hegemony. Originating in the aftermath of the Soviet Union’s collapse and shaped by intellectual exchanges across Russia, Italy, and France, Red-Brownism has developed as a metapolitical movement with strong ties to Eurasianist thought, advocating for a multipolar world order. The research explores Red-Brownism as a hub for ideological dissent, analyzing its internal divergences and its role in shaping geopolitical narratives, particularly in light of the Russo-Ukrainian War and the re-election of Donald Trump. Special attention is given to the competing visions within Eurasianism, highlighting the tensions between Red-Brown Eurasianists and those engaging with Trumpist conservatism. Through an analysis of key thinkers and metapolitical discourse, the article investigates Red-Brownism’s trajectory, internal tensions, and its potential impact on global politics.